(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
In January 1892, Gilberto Crespo y Martínez published a book entitled Belgium: commercial museums, consular service, education and industrial and commercial propaganda. Why prepare a publication on a small European kingdom, where the widespread practice was to study English empires and Austro-Hungarian or the French and American fast-growing states? The aim of this paper is to locate the reason for the approach to the Belgian model as an option within the economic and trade policy during the Porfirio Díaz regime. A further aspect was to evaluate what was the impact of his experience on himself and in his long career as a diplomat.